The Completeness of Product Data in Infoboxes in Different Language Versions of Wikipedia - Lewoniewski , Włodzimierz; Kasprzak , Aleksandra; Węcel , Krzysztof; Abramowicz , Witold (Studia Oeconomica Posnaniensia, 2018)
Wikipedia is currently one of the most popular sources of knowledge. Many articles in this multilingual encyclopaedia contain information about different products, such as cars, movies, computer games or mobile phones. Articles about these goods can be edited independently in various languages, and differences in the content added by users (including anonymous ones) can be observed. An article usually contains an infobox, which in a concise way presents the most important facts from the article. Readers can use infoboxes to get the most important information about a product without analysing the content of the entire article. Additionally, data extracted from an infobox can be used to enrich other popular databases, such as DBpedia. For this reason, it is particularly important to verify the data quality provided by users, where quality can be characterized by metrics such as timeliness, correctness and completeness. This paper examines the completeness of product data from various groups from different language versions of Wikipedia. The results of the study can be applied in practice to enrich information about products.